A Hierarchical Framework of Challenges for Blockchain Adoption in Public Services. Implications for decision-makers - Yogesh Dwivedi (Scandinavian Journal of Information Systems, 2023)
This study attempts to identify critical challenges for blockchain adoption in government, particularly public-service delivery in India, a developing country context. Through an extensive literature review and focus-group discussions with policymakers and blockchain experts, we have identified 12 adoption challenges for Blockchain in public service delivery. We then collected data and analysed using interpretive structural modeling and Cross-Impact Matrix Multiplication Applied to Classification (MICMAC) Analysis to develop a hierarchical framework of the challenges. Our findings indicate that governments must first ensure legislative support for blockchain-based transactions. This research contributes to information systems strategic planning literature and provides a framework for policymakers to craft a strategic approach to facilitate blockchain adoption.